PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LERANING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN MENYIMAK BAHASA INDONESIA PESERTA DIDIK KELAS V SD NEGERI 1 WAY KANDIS - Niken Maulidya; Siti Nurjanah; Diana, Siska Mega; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the low listening skills in the Indonesian language among fifth-grade students at SD Negeri 1 Way Kandis. This study aims to determine the effect of the Problem-Based Learning model assisted by audio-visual media on students’ listening skills. The research method used is a quasi-experimental design with a population of 82 students and a sample of 55 students, selected using a random sampling technique. Data were collected using test and non-test techniques, including observation sheets. The results of hypothesis testing using simple linear regression analysis showed that the use of the Problem-Based Learning model assisted by audio-visual media had a significant effect on the Indonesian language listening skills of fifth-grade students at SD Negeri 1 Way Kandis.